Implementasi Pendekatan Saintifik untuk meningkatkan Kemampuan Pemecahan Masalah Matematika Pada Materi Persamaan Garis Lurus di MTs Negeri 3 Cilacap - Mahmudin Mahmudin (Lembaga Bale Literasi, 2022)
This study aims to determine the effectiveness of the scientific approach in improving mathematical problem-solving skills in straight line equations. This research is a classroom action research with 22 students as research subjects. This study consisted of two cycles with each cycle consisting of 2 meetings. The instruments used are in the form of questionnaires, interview sheets, and observation sheets. The data analysis technique used descriptive qualitative. The results of the analysis show that: 1) the scientific approach is effective to improve students' mathematical problem-solving abilities; 2) The problem-solving ability in the first cycle showed a fairly good category with an average score of 56.37 with the completeness of 49.99%; 3) The problem-solving ability in the second cycle showed a very good category with an average score of 81.81 with the completeness of 93.17%.